GOLD WIRE FOR BONDING IN SEMICONDUCTOR DEVICE - YAMAMOTO TAIYO; KUJIRAOKA TAKESHI (1991)
PURPOSE:To obtain the gold wire for bonding in a semiconductor device free from disconnection caused by stress concentration directly upon a gold ball by limiting its grain size by the relationship between the grain size in the heat affected zone and the initial grain size in the wire. CONSTITUTION:As for the grain size of a gold wire having about >=99% high purity, the ratio of 1<(the average grain size in the heat affected zone)/(the initial grain size in the wire) <=2.5 times is regulated. The above crystals can be formed by controlling the heat treatment and wire drawing. In this way, the gold wire in which external stress is uniformly dispersed and the disconnection caused by stress concentration directly upon a gold ball is prevented can be obtd.